Urban Displacements: The Azorean Diaspora and the Rebranding of Portuguese Identity in Boston - Cordeiro, Graça Índias; Formato, G. (International LSA Conference 2026: Voices and Visions: Lusophone Communities in the Global Landscape, 2026)
On August 15, 1932, the Portuguese American Civic League (PACL) organized a massive celebration in Inman Square (Cambridge/Somerville, MA) for the V Centenary of the “discovery” of the Azores. With over 75,000 participants and spectators, the parade featured floats for each of the nine islands, Azorean music, dances, and dignitaries—affirming a strong Azorean-American cultural presence in the streets and institutions of the only Boston’s Portuguese neighborhood. By contrast, a 2014 Portuguese Youth Conference hosted by PACL and organized by the Boston Portuguese Festival (2006-2017) revealed a striking shift: images of the Azores were overshadowed or erased, replaced by symbols of continental Portugal, colonial narratives, outdated folkloric tropes, and nationalist discourse echoing Estado Novo propaganda. Children were prompted to "save Portuguese culture" through purity tests and nostalgic stereotypes, while the local community was subtly blamed for cultural “loss.” This paper traces the symbolic transformation of Portuguese American public celebrations from community-based Azorean expressions to a centralized, depoliticized, and tourism-driven spectacle at Boston’s City Hall Plaza, beginning in 2018. Using ethnographic fieldnotes, photographs, local media, and institutional materials, we analyze two parallel processes: (1) the erasure of Azorean cultural specificity in diasporic identity narratives; and (2) the deterritorialization of ethnic festivity from neighborhood spaces to a state-sponsored downtown stage. By focusing on parades, folklore, and performative nationalism, this case study explores how bottom-up expressions of belonging are reconfigured by top-down ideologies—highlighting tensions between local memory, diaspora identity, and the commodification of “Portugueseness” in the global landscape.